Pertanggungjawaban Pidana Terhadap Pelaku Penyakit Bipolar dalam Penyebarluasan Tindak Pidana Pornografi - Fachrozy, Dicky; Panjaitan, Budi Sastra (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The aims to analyze the criminal responbility of sufferers of bipolar disorder, in this case the perpetrators distribute pornographic videos of victim, in law the 2008 Pornography Law regulates this, therefore the victim wants to sue the perpetrator to court. And in Law No. 18 of 2014 concerning mental health Article 71 paragraph 1 reads “For the sake of law enforcement, a person suspected ODGJ who committed a crime must get a Mental Health examination. “For this reason, the purpose and scope of the research focused on this article. This study usednormative and qualitative methods with the nature of prescriptive research. The results i found were from the evidence as the statemenr the perpetrator can prove he has bipolar disorder, therefore in the Criminal Code Article 44 paragraph 1 states that no one can be punished for carrying out an act for which he cannot be held accountable, because his mind is imperfect or he has a change of mid. Bipolar discorder is adjusted to the conditions that accompany the sufferer in certain legal cases. However, in this case it cannot be equated that every criminal act commited by a person wuth bipolar disorder cannot be partially responsible.